«Norte contra Sur». Análisis comparativo sobre ofrendas rituales andinas - Fernández Juárez, Gerardo (Revista Española de Antropología Americana, 2010)
Through a comparative analysis, this paper tries to delimitate the differences and similarities between the ritual systems in Central and Southern Andes, with special emphasis on the role of ritual specialists and the typology of offerings. However, the purpose of this pages is not so much to make up a kind of comparative tables, but rather to present a collection of contrasted data, allowing further progress in this area.
Keywords: Offers; Mesas; Ritual specialists; Aymaras; Quechuas; Kallawayas